Relevant Issues of Planning Bioequivalence Studies of Drugs with a Narrow Therapeutic Range - D. P. Romodanovsky (Регуляторные исследования и экспертиза лекарственных средств)
In order to be registered, generic drugs with a narrow therapeutic range have to undergo bioequivalence or therapeutic equivalence studies. In most cases, comparative pharmacokinetic studies and demonstration of bioequivalence between the test and the reference products are sufficient for this group of drugs. However, there is no established official definition in Russia for the group of drugs that are regarded as having a narrow therapeutic range. Evaluation of bioequivalence of such drugs has to be performed providing for narrower confidence intervals, which entails certain problems at the stage of bioequivalence study planning. Finding solutions to the problems stated above is of great importance. The aim of the study was to develop approaches to planning bioequivalence studies of drugs with a narrow therapeutic range. Materials and methods: the paper analyses the results of 33 bioequivalence studies of drugs with a narrow therapeutic range, in which Cmax, AUC0-t, and tmax were calculated. Intra-individual variation and weighted mean intra-individual variation of Cmax and AUC0-t were estimated in the study. Statistical processing was performed using IBM SSPS Statistics v.25. and Microsoft Office Excel 2016. Results: the paper summarises criteria for categorising drugs as having a narrow therapeutic range and describes general requirements for assessing their bioequivalence. A number of bioequivalence studies of generic valproic acid, carbamazepine, levothyroxine, tacrolimus, and cyclosporine products which meet the criteria for drugs with a narrow therapeutic range, were analysed retrospectively. The data on their pharmacokinetics and intra-individual variation were calculated. It also summarises requirements for bioequivalence evaluation of drugs with a narrow therapeutic range. The paper gives product-specific recommendations for performing bioequivalence studies. Conclusion: the study helped to formulate approaches to the planning of bioequivalence studies of generic drugs with a narrow therapeutic range using the examples of valproic acid, carbamazepine, levothyroxine, tacrolimus, and cyclosporine.